2015
DOI: 10.1080/21645515.2015.1074362
|View full text |Cite
|
Sign up to set email alerts
|

Research and development of therapeutic mAbs: An analysis based on pipeline projects

Abstract: As the subject of active research and development (R&D) in recent decades, monoclonal antibodies have emerged among the major classes of therapeutic agents for treatment of many human diseases, especially cancers, infections, and immunological disorders. This article surveys the landscape of R&D projects of therapeutic monoclonal antibodies (mAbs), which are mostly used for disease immunotherapy, from a number of perspectives, including therapeutic indications, development phases, participants, and citation of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
1
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(25 citation statements)
references
References 49 publications
(45 reference statements)
1
22
1
1
Order By: Relevance
“…Antibodies have evolved from being ancillary biochemical reagents in laboratory research to taking center stage as powerful drugs that are used in the clinic to treat cancer and immune-mediated disorders (1, 2). By the end of 2014, the list of 47 antibody therapeutics approved and marketed in the US and EU was growing at an average approval rate of 4 new products per year (3).…”
Section: Introductionmentioning
confidence: 99%
“…Antibodies have evolved from being ancillary biochemical reagents in laboratory research to taking center stage as powerful drugs that are used in the clinic to treat cancer and immune-mediated disorders (1, 2). By the end of 2014, the list of 47 antibody therapeutics approved and marketed in the US and EU was growing at an average approval rate of 4 new products per year (3).…”
Section: Introductionmentioning
confidence: 99%
“…The crystallizable or constant fragment (Fc) region of mAbs determines their effector function through the ability to bind Fc gamma receptors (FcγR) expressed on endogenous cells. 14…”
Section: S Truc Tur Al and Fun C Tional Fe Ature S Of Antibod Ie Smentioning
confidence: 99%
“…In most cases in vivo models can be limited in their ability to predict efficacy in humans, particularly due to differences in the pharmacokinetics of the molecules between humans and model animal species [110]. Geng et al reported that a large percentage of antibodies for anti-infective indications are ended in the early stage of discovery making them a high risk category in drug development [35]. Challenges in clinical efficacy and pharmacokinetics can be overcome by choosing appropriate format for the indication.…”
Section: Gram Positive Bacteria Targetsmentioning
confidence: 99%